Prescribing Cold: The Science and Practice of Cryotherapy in Dental Medicine - Anuj Singh Parihar; Kamal Hotchandani; Arunkumar Sajjanar; Sonam Parakh; Himani Tiwari; Lipsa Bhuyan (Wolters Kluwer Medknow Publications, 2024)
Cryotherapy, or the use of low temperatures for medical treatment, has gained interest in dentistry for its potential therapeutic benefits. This review article delves into the rationale, applications, advantages, and limitations of cryotherapy in dentistry, shedding light on its future prospects in the field.